Is Technical Assistance under Free Trade Agreements WTO-Plus? A Review of Japan-ASEAN Economic Partnership Agreements - Shintaro Hamanaka (Asian Development Bank (ADB), 2011)
What kind of technical assistance and capacity building benefits do developing countries enjoy if they sign a free trade agreement (FTA) with developed countries? This is a frequently asked question among developing country officials involved in FTA policymaking. While we tend to normatively insist that an FTA should lead to a win-win situation for all contracting parties and that developed members should provide technical assistance to developing partners so that the latter can maximize the benefits and minimize the costs of an FTA, empirical assessments of technical assistance mechanisms under FTAs have not been thoroughly conducted. This paper presents a detailed textual analysis of World Trade Organization (WTO) Agreements and several FTAs in Asia, and identifies how much additional technical assistance developing member countries can enjoy if they enter into FTAs with developed countries.
hdl:11540/1993
Keywords: F51; F53; K33; 330; Technical Assistance; FTAs; North-South Cooperation; WTO Agreements